Tradução e validação do Questionário de Avaliação do Preparo para a Transição (TRAQ) para o português brasileiro em uma população de adolescentes e adultos jovens com doença reumática crônica - Anelli, Catherine Gusman [UNIFESP] (2017)
Objective: To translate and validate a Brazilian-Portuguese version of the Transition Readiness Assessment Questionnaire (TRAQ) in a population of transitional youth with chronic rheumatologic disorders. This questionnaire evaluates the readiness of the patient for making the transition from the pediatric health service to adult care. Methods: We followed the 4-phase methodology for translation and validation of generic questionnaires including translation, back translation, pilot testing and clinical validation of the final instrument. The Cronbach's alpha coefficient was used to assess the overall internal consistency of the final instrument. Results: We enrolled 150 patients with an average age of 17.0 years (SD = 2.2 years, range 14-21years) for the final validation of the instrument. There were 71 patients with juvenile systemic lupus erythematosus (JSLE) (47.3%), 64 with juvenile idiopathic arthritis (JIA) (42.7%) and 15 with juvenile dermatomyositis (JDM) (10%). An initial analysis identified the dimension "Talking with providers" consisting of two questions as not fitting the translated questionnaire due to a very high ceiling effect and had to be excluded. All other translated items favorably contributed to the overall consistency of the final instrument and deleting that dimension did not result in a substantial increase in the Cronbach Alpha. Conclusions: With the exception of one dimension our Brazilian-Portuguese translated version of the TRAQ could be validated in a population of transitional youth with chronic rheumatologic disorders. It is a non-specific disease questionnaire, thus it can be used to evaluate the transition readiness of other Brazilian patients with chronic diseases.